Practical Research on Mixed Teaching Reform of Linux Operating System Course (Contemporary Education and Teaching Research, 2024)
With the rapid development of technology and the diversification of educational needs, the traditional teaching mode can no longer fully meet the requirements of modern education. Linux is widely used in servers, cloud computing, network infrastructure, embedded systems high-performance computing, etc. As an important part of the field of computer science and information technology, the teaching method of the Linux operating system needs to be constantly innovated and improved to adapt to this change. to adapt to this change. The hybrid teaching mode is a teaching method that combines online and offline teaching resources, which provides new possibilities to improve the teaching quality of Linux courses and the learning effect of students. The purpose of this paper is to discuss the reform practice of Linux operating system courses under the hybrid teaching mode, including the teaching method, course content, evaluation mechanism, and the cultivation of practical application ability.